2015
DOI: 10.1002/mnfr.201500181
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin B2 attenuates neurological deficits and blood–brain barrier disruption in a rat model of cerebral ischemia

Abstract: PB attenuates neurological deficits and BBB disruption in a rat model of cerebral ischemia, and the neuroprotection of PB is associated with activation of NF-E2-related factor pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…It is reported that Nrf2 pathway is an important target in the treatment of neurodegenerative diseases (Wu et al, 2015). Under normal physiological conditions, Nrf2 binds to Keap1, a cysteinerich protein, located in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that Nrf2 pathway is an important target in the treatment of neurodegenerative diseases (Wu et al, 2015). Under normal physiological conditions, Nrf2 binds to Keap1, a cysteinerich protein, located in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance with the results of previous studies, which suggest that physiologically active components in hawthorn such as Procyanidin B2 might act as a mechanism for lowering oxidative stress [ 65 ]. Procyanidin B2 possesses strong free radical scavenging activity and antioxidant activity [ 66 ], and it has been demonstrated that Procyanidin B2 protects human colonic cells against oxidative stress through activation of the transcription factor Nrf2 via regulation of extracellular signal-regulated kinases (ERKs) and p38 signaling [ 67 ]. The data suggest that the protective action of Procyanidin B2 in hawthorn is related to the induction of antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…Transient MCAO MCAO was induced as described previously [25,26] , with minor modifications. Briefly, the left common carotid artery and the external carotid artery were exposed and ligated in the anesthetized animals.…”
Section: Animal Modelmentioning
confidence: 99%